The Momo Challenge: Exploring the Emergence of a Major Online Demonic Hoax - Alderton, Zoe (Journal for the academic study of religion, 2021)
From 2018-2019, the spectre of Momo haunted the internet. Momo is depicted as a gaunt Japanese woman with long black hair, an enlarged mouth, and bulbous, haunting eyes. Allegedly, Momo responds to those who text her phone with violent imagery and explicit threats. She also encourages children to self-harm and shows them triggering images of gore, sometimes interspersed amidst innocent cartoons. Of course, Momo is not real and no one has hurt themselves in response to her ‘challenges’. From the start, Momo was very clearly a novel urban legend whose influence was magnified in the popular press and by their deeply-held suspicion of internet predators, peer pressure, and an online world in which technology makes any kind of sinister attack possible. Momo is thus an important case study in establishing the recent history of online demon fear, which feeds into broader trends surrounding ‘Satanic panic’ gateways into the occult. This article positions Momo as the latest manifestation of a fear that children are especially susceptible to evil, and that parents must remain vigilant to the corrupting forces of the demonic.